Let's solve this problem step-by-step.
STEP-BY-STEP SOLUTION:
We will be using simultaneous equations to solve this problem.
Let's first establish the equations which we will require to solve this problem as displayed below:
Let number no. 1 = x
Let number no. 2 = y
Equation No. 1 -
x + y = 59
Equation No. 2 -
x - y = 11
To begin with, we will make ( x ) the subject in the first equation as displayed below:
Equation No. 1 -
x + y = 59
x = 59 - y
Next we will substitute the value of ( x ) from the first equation into the second equation to solve for ( y ) as displayed below:
Equation No. 2 -
x - y = 11
( 59 - y ) - y = 11
- y - y = 11 - 59
- 2y = - 48
y = - 48 / - 2
y = 48 / 2
y = 24
Then we will substitute the value of ( y ) from the second equation into the first equation to solve for ( x ) as displayed below:
Equation No. 1 -
x = 59 - y
x = 59 - ( 24 )
x = 35
FINAL ANSWER:
Therefore, the two numbers are 35 and 24.
Please mark as brainliest if you found this helpful! :)
Thank you <3